Comparative Study of Delay Analysis Techniques and Its Effectiveness in Application in Construction Projects - Ahmed, Jamal (Digital Repository of Theses, 2025)
The attached literature review examines the existing techniques for analysing delays in construction projects, focusing on their effectiveness in accurately assessing delay claims. The construction industry frequently faces delays, which lead to disputes over responsibility and financial claims. This review highlights the complexity of delay claims, which necessitates precise analysis to determine causation and allocate responsibility. The study evaluates over nineteen delay analysis techniques (DATs), identifying limitations such as inconsistencies and lack of adaptability to specific project contexts, which often hinder accurate claim settlements. The research assesses the prevailing delay analysis methods, including As-Planned vs. As-Built, Time Impact Analysis, and Window Analysis, identifying critical factors that affect their accuracy and applicability in real-world projects. Through case studies and judicial precedents, the review underscores the importance of comprehensive record-keeping (e.g., schedule updates, resource usage, communication records) to substantiate claims effectively. Moreover, the study proposes a refined approach to delay analysis that considers the practical constraints and unique circumstances of each project, aiming to reduce subjective interpretations. A significant contribution of the review is its proposal of a structured framework that addresses the common deficiencies in delay analysis. This framework, validated through expert feedback and practical applications, emphasizes clarity, completeness, accuracy, and cost-effectiveness. By integrating best practices with advancements in delay analysis, the study offers a systematic methodology to improve claims resolution processes, benefitting contractors, owners, and legal professionals involved in construction dispute management. The review concludes with a call for ongoing improvements in delay analysis methods, emphasizing the role of advanced technologies and data-driven approaches in enhancing reliability and efficiency in construction project management.